Prilaku Komsumsi Terhadap Nilai-Nilai Islam - SITI RAIHANUN; Andri Martiana (Al-Qardhu, 2025)
Consumption is an economic activity that encompasses not only material dimensions but also reflects individual values, ethics, and spirituality. In Islam, consumption behavior is not merely about fulfilling worldly needs, but also serves as a form of devotion to Allah SWT, guided by the principles of justice, balance (wasathiyah), moderation (qana’ah), and the prohibition of extravagance (israf). This study aims to examine consumption behavior from the perspective of Islamic values using a descriptive-qualitative approach through library research. The findings reveal that Islam emphasizes ethical principles in consumption, including the consumption of lawful (halal) and wholesome (thayyib) goods, avoiding excessive consumerism, and considering social obligations through zakat and infaq. Consumption in Islam is not solely intended for personal gratification but is also directed toward achieving collective welfare and life blessings. Islamic values offer a moral framework that regulates consumption behavior and helps prevent the excesses of hedonism and materialism characteristic of modern consumerism. Therefore, internalizing Islamic values in consumption is essential for creating a just and sustainable economic order. This study is expected to serve as a reference for developing an Islamic model of consumption that is relevant to contemporary challenges.